Bimetallic Fe and Co supported on the N‐doped mesoporous carbon frameworks with enhanced oxygen reduction reaction performance via high‐gravity technology. Issue 6 (9th February 2021) - Wu, Guangping; Shi, Jinhua; Dong, Hongbo; Nie, Yao; Wang, Yanzhong; Chen, Yanjun; Li, Dan; Linghu, Yaoyao; He, Zhenfeng; Wang, Chao; Guo, Li
Abstract: The exploitation of high‐efficiency, inexpensive, as well as durable electrocatalysts for the oxygen reduction reaction (ORR) is of vital importance for the commercialization of fuel cells. In this study, we prepared an efficient non‐precious ORR electrocatalyst via high‐gravity technology. The results of physical characterization revealed that the Fe atoms could be uniformly dispersed on the Fe/Co/N‐MCF catalyst via the high‐gravity technology. The X‐ray photoelectron spectroscopy demonstrated that the Fe can be combined with N from the ZIF‐67 to form the Fe‐N x structures, which has already been confirmed to be acted as validly ORR active sites. The electrochemical testing results showed that the Fe/Co/N‐MCF catalyst obtained via high gravity technology expressed a 24 mV positive than commercial Pt/C in terms of half‐wave potential. Moreover, Fe/Co/N‐MCF catalyst exhibited an excellent anti‐ethanol activity and durability, its current density only decays 2.6%, far lower than 23.3% of commercial Pt/C after 10, 000 s chronoamperometry aging test. Abstract : The high gravity technology was introduced to prepare a high efficiency non‐precious oxygen reduction reaction catalyst Fe/Co/N‐MCF, which surpassed the commercial Pt/C catalyst about 31 mV in terms of the E 1/2 . The enhanced activity can be ascribed to the Fe atoms uniformly dispersed on the Fe/Co/N‐MCF catalyst and combined with N to form the Fe‐N x structure via the RPB.